Hypertensive disorders of pregnancy and long‐term cardiovascular health: FIGO Best Practice Advice. (12th January 2023) - Poon, Liona C.; Nguyen‐Hoang, Long; Smith, Graeme N.; Bergman, Lina; O'Brien, Patrick; Hod, Moshe; Okong, Pius; Kapur, Anil; Maxwell, Cynthia V.; McIntyre, Harold David; Jacobsson, Bo; Algurjia, Esraa; et al.
Abstract: Hypertensive disorders of pregnancy (HDP) are the most common causes of maternal and perinatal morbidity and mortality. They are responsible for 16% of maternal deaths in high‐income countries and approximately 25% in low‐ and middle‐income countries. The impact of HDP can be lifelong as they are a recognized risk factor for future cardiovascular disease. During pregnancy, the cardiovascular system undergoes significant adaptive changes that ensure adequate uteroplacental blood flow and exchange of oxygen and nutrients to nurture and accommodate the developing fetus. Failure to achieve normal cardiovascular adaptation is associated with the development of HDP. Hemodynamic alterations in women with a history of HDP can persist for years and predispose to long‐term cardiovascular morbidity and mortality. Therefore, pregnancy and the postpartum period are an opportunity to identify women with underlying, often unrecognized, cardiovascular risk factors. It is important to develop strategies with lifestyle and therapeutic interventions to reduce the risk of future cardiovascular disease in those who have a history of HDP. Synopsis: Pregnancy and the postpartum period are an opportunity for identification of and intervention for underlying cardiovascular risk factors.